Sliding mode observer for sensorless control of surface permanent magnet synchronous motor equipped with LC filter. Issue 4 (1st April 2019) - Xu, Yongxiang; Wang, Minghui; Zhang, Wentao; Zou, Jibin
Abstract : This study proposes a sliding mode observer (SMO) based method for sensorless speed control of surface permanent magnet synchronous motor equipped with LC filter. To deal with side effects of pulse width modulation technique, LC filters are equipped between inverters and motors in some industrial applications. Therefore, filter input currents rather than stator currents will be measured by current sensors on the inverter board. Sensorless operation becomes complicated due to the differences between filter input and stator currents. When only inverter‐side current sensors are installed, the mathematical model of the LC filter should be considered. Hereby, the proposed SMO takes the LC filter into consideration, so additional measurement of stator currents is not necessary. Back electromotive forces of the PMSM are estimated by the SMO, and the rotor speed and position are calculated by the phase locked loop. The proposed approach features simplicity, and it is suitable for medium‐ and high‐speed ranges. Simulation and experimental results confirm the effectiveness of the proposed method.